The Good, the Bad, and the Ugly: Impact of Negative Interest Rates and QE on the Profitability and Risk-Taking of 1600 German Banks - Florian Urbschat (Center for Economic Studies and ifo Institute (CESifo), 2018)
The recent negative interest rate policy (NIRP) and quantitative easing (QE) programme by the ECB have raised concerns about the pass-through of monetary policy. On the one hand, negative rates could lead to declining bank profitability making an expansionary monetary policy contractionary. Also, if interest rates are too low for too long banks could be induced to take too much risky credit. On the other hand, several economists argue that there is nothing special about negative interest rates per se. This paper uses a large micro level data set of the German bank universe to examine how banks behave in this uncharted territory. The evidence found suggests that bank's business model, i.e. the share of overnight deposits, plays a crucial role. While some banks may benefit in the short run via for instance reduced refinancing costs or lower loan loss provisions, many banks with high deposit ratios face lower net interest income and lower credit growth rates. If continued for too long QE and NIRP erode bank profits for most banks eventually.
Keywords: C53; E43; E52; G11; G21; 330; negative interest rate policy; banks' profitability; net interest rate margin; risk-taking channel